2006
DOI: 10.1002/lt.20849
|View full text |Cite
|
Sign up to set email alerts
|

Impact of donor age on survival and fibrosis progression in patients with hepatitis C undergoing liver transplantation using HCV+ allografts

Abstract: Studies have suggested that the use of hepatitis C virus (HCV)-positive (HCVϩ) donor allografts has no impact on survival. However, no studies have examined the effect that HCVϩ donor histology has upon recipient and graft survival. We evaluated the clinical outcome and impact of histological features in HCV patients transplanted using HCVϩ livers. We reviewed all patients transplanted for HCV at our institution from 1988 to 2004; 39 received HCVϩ allografts and 580 received HCVnegative (HCVϪ) allografts. Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 23 publications
2
71
2
1
Order By: Relevance
“…Three-year graft survival rates were similar among both patient populations [13]. Other more recent small trials have continued to support the notion of using HCV+ grafts in HCV+ recipients without major clinical detriment [14,15]. The purpose of this study is to investigate the long-term effect of liver transplantation using HCV+ donors including data from the modern era of organ allocation, transplantation and immunosuppression.…”
Section: Introductionmentioning
confidence: 92%
“…Three-year graft survival rates were similar among both patient populations [13]. Other more recent small trials have continued to support the notion of using HCV+ grafts in HCV+ recipients without major clinical detriment [14,15]. The purpose of this study is to investigate the long-term effect of liver transplantation using HCV+ donors including data from the modern era of organ allocation, transplantation and immunosuppression.…”
Section: Introductionmentioning
confidence: 92%
“…Demonstrating a negative impact of older donor age (> 50 years) on survival and fibrosis progression in patients transplanted with HCV+ organs. According to the current evidence, using HCV+ grafts from young donors (< 50 years) for HCV recipients can produce good results, but further experience is required to establish the validity of this approach [65] . The influence of co-infections on HCV recurrence has been investigated by a number of groups.…”
Section: Hcv Positive Donors and Co-infectionsmentioning
confidence: 99%
“…One approach to expand the pool of organs for transplantation is to use grafts from extended-criteria donors, such as HCV-positive donors. Several studies have reported no differences in outcomes with the use of HCV-positive grafts in comparison with the use of non-infected grafts (Marroquin et al, 2001;Vargas et al, 1999;Velidedeoglu et al, 2004), although donor age has recently been recognized to play an important role after transplantation with HCV-positive grafts (Khapra et al, 2006). In addition, it is important to note that grafts from genotype 1 donors should not be allocated to recipients infected with genotypes 2 or 3, in which antiviral therapy is significantly more effective than for genotype 1, and the introduction of the latter genotype may be detrimental for the patient's outcome.…”
mentioning
confidence: 99%